PERILAKU MASYARAKAT DALAM BUANG AIR BESAR (Study Kasus di Desa Ngrawan Kecamatan Berbek Kabupaten Nganjuk Tahun 2014) - Nita Melina Wati; Sri Mardoyo; Ferry Kriswandana (Poltekkes Kemenkes Surabaya, 2014)
Dealing with defecation remains an important aspect in envirinmental health programs. Accordingto the Expert Commitee on Environmental Health of WHO, defecation was designated as a top priority thatmust be dealt with in the context of environmental health, primarily in rural areas. Imporer defecation maycontaminate soil and drinking water sources. The purpose of the research was to determinane thebehavior of people in relation to defecation.This research employed a descriptive method. Data were collected by observation andquestionnaire. The size of samples to be observed in this study was 89 heads of household. The datacollected were subSequently analyzed descriptively where description and discussion were based on theanswers on the questionnaire.Results of the study on people's behavior in Ngrawan Village, Berbek Subdistrict, Nganjuk Districtindicated that 49.44% (44) of the respondents were aged 25-35 years, 47.29% (42) of respondents hadJunior High School Education, 39.32% (35) of the respondent worked as peasants, 41.57% (37) ofrespondents had low economic status. About 28.09% (25) of the respondents had inadequate knowledge.About 42.70% (38) of the respondents didn't take any action adequately, and 39.33% .(35) ) of therespondents had poor behavior.It is suggested that the primary health center performs a triggedng initiative to boost people'sunderstanding. This way people will know, understand, and implement hygienic and healthy livingbehavior, especially in relation to defecation. Pople need to hold SOCialgatherings (such as women'slottery club) or Jimpitan to facilitate the ideals that at the end everybody have their own latrines